PENERAPAN METODE DENGAR UCAP PADA PEMBELAJARAN BAHASA ARAB KELAS VII DI MTS AS-SYAFI’IYAH PINGGIR - Azhari, Mohd. Fikri; Hasby, Hasby (Institut Agama Islam Negeri Pontianak, 2020)
Abstract. This research is an effort to make it easier to learn Arabic in class VII students at MTs As-syafi’iyah Pinggir, Bengkalis District. The first question that will be answered through this research is; whether the application of the audiolingual method can make it easier to learn Arabic in MTs As-syafi’iyah Pinggir ?. To answer this question, this research uses class action research (PTK) for 2 cycles. The purpose of this study was to make it easier to learn Arabic in class VII students of MTs As-syafi’iyah Pinggir, Kab. Bengkalis through the application of the audiolingual method. Based on the analysis of the data obtained that the application of the audiolingual method in Arabic learning can improve Arabic speaking exercises for grade VII students at MTs As-syafi’iyah Pinggir Kab. Bengkalis. This is evidenced by the average value in the first cycle of students who completed 13 students equivalent to 60% and 10 students who did not complete the equivalent of 40%, while the second cycle of students who completed 19 students was equivalent to 85% and students who did not complete a total of 4 students is equivalent to 15%. The application of the audiolingual method has a good influence in learning Arabic, this can be proven that the audiolingual method can improve the ability to speak Arabic in grade VII students at MTs As-syafi’iyah Pinggir, Kab. Bengkalis because it can increase the percentage of students completeness in cycles 1 and 2 by experiencing an increase of 25%. Kata Kunci: Audiolingual Method, Action Research, Arabic Language